The Effectiveness of Jigsaw Models with Interactive Video Media in Improving Learning Outcomes of End-of-Day Signs - Andi Muhammad Raihan Al-Mulk; Muhaemin Muhaemin; Makmur Makmur; Usman Aksan (South Sulawesi Education Development (SSED), 2026)
This study aims to examine the effectiveness of applying the Jigsaw-type Cooperative Learning Model, integrated with interactive videos, in improving student learning outcomes for the Signs of the Last Day material in grade VI at SDN 53 Sawerigading. This class action research is conducted in two cycles, comprising the stages of planning, implementation, observation, and reflection. The results showed that using the Jigsaw model with interactive videos increased student learning outcomes from an average score of 70 (52% completeness) in Cycle I to 90 (88% completeness) in Cycle II, indicating that its implementation was effective. This improvement shows that combining cooperative learning with interactive videos can make the learning process more active, engaging, and meaningful for students.